Pengaruh Profitabilitas, Solvabilitas, Size Perusahaan Terhadap Timeliness Laporan Keuangan - Fery Derianto; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to provide empirical evidence regarding the factors that affect the timeliness of financial reporting on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Timeliness is information that ready to be used before losing meaning by companies who use financial statements and their capacity is still available for make a decision. The determinant factors in this study are profitability, solvency and firm size. By using purposive sampling method, obtained research samples of 30 companies. The dependent variable of this study is timeliness measured by the date the audited annual financial statement is submitted to BAPEPAM by using a dummy variable. The independent variables in this study are profitability, solvency, and firm size. Profitability is measured using return on assets (ROA), solvency is measured by the debt to assets ratio (DAR), and firm size is measured by natural log of total assets. The analysis technique used is multiple regression analysis. The results of this study are the solvency has a significant and positive effect on the timeliness of financial reporting, while profitability and company size do not have an influence on the timeliness of financial reporting